2020
DOI: 10.1111/irv.12708
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus acute respiratory infection‐associated hospitalizations in preterm Mexican infants: A cohort study

Abstract: Background Respiratory syncytial virus (RSV) is the leading cause of severe acute respiratory infections (ARI) in preterm infants. The incidence of RSV‐associated hospitalizations has not been defined in Mexico. Objectives To determine the incidence of ARI‐ and RSV‐associated hospitalizations in preterm infants during the first year of life. Methods Prospective cohort study of 294 preterm infants followed up through monthly telephone calls and routine outpatient visits. Hospitalized children were identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The mortality in infants with risk factors was greater (6.6%) in comparison with that of infants without risk factors (2.3%) [9]. In another recent Mexican study of a cohort of 294 preterm infants, the RSV admission frequencies were estimated to be 13.6% in BPD, 16.5% in CHD, and 4.1% in otherwise healthy preterm infants [19]. In another study, children with risk factors such as premature birth, a pre-existing respiratory disease, or CDH, have higher morbimortality if coinfected with adenovirus (RSV mortality of 1.1% and 2.7% in coinfection with adenovirus) [10].…”
Section: Discussionmentioning
confidence: 92%
“…The mortality in infants with risk factors was greater (6.6%) in comparison with that of infants without risk factors (2.3%) [9]. In another recent Mexican study of a cohort of 294 preterm infants, the RSV admission frequencies were estimated to be 13.6% in BPD, 16.5% in CHD, and 4.1% in otherwise healthy preterm infants [19]. In another study, children with risk factors such as premature birth, a pre-existing respiratory disease, or CDH, have higher morbimortality if coinfected with adenovirus (RSV mortality of 1.1% and 2.7% in coinfection with adenovirus) [10].…”
Section: Discussionmentioning
confidence: 92%
“…Infants with BPD had increased risk of severe RSV disease relative to those without BPD [ 28 , 29 ]. Furthermore, low gestational age (<32 wk) and low birth weight (<1500 g) are critical risk factors for infant RSV hospitalization [ 30 , 43 , 44 , 45 ]. Consistent with these clinical observations, we found that young adult mice that were exposed to hyperoxia at the saccular stage of neonatal lung development carried on persistent lung injury including impaired alveoli and focal fibrotic changes and predisposed to more severe RSV disease.…”
Section: Discussionmentioning
confidence: 99%
“…The virus can cause its effects on the cardiac system through different ways of direct infection, binding to the functional receptors of ACE2, and immune damage. Cardiomyocyte infection by COVID-19 following by virus replication can lead to tissue degeneration, necrosis ( Benítez-Guerra et al, 2020 ), and apoptosis ( Heffernan et al, 2020 ). Indeed, the viral infection of COVID-19 can cause extracellular matrix remodeling leading to the production of fibrotic scars.…”
Section: Cytokine Stormmentioning
confidence: 99%
“…The cardiac damage measured by increased levels of high-sensitivity troponin I has been mentioned to be found in about 20% of COVID-19 patients ( Heffernan et al, 2020 ). Besides cardiac troponin I, increased levels of other laboratory cardiac markers have been seen in patients, such as higher levels of CK, creatine kinase-muscle/brain activity, myoglobin, alpha-hydroxybutyrate dehydrogenase (α-HBDH), N-terminal pro-brain natriuretic peptide (NT-proBNP), and AST ( Benítez-Guerra et al, 2020 ). Cardiac markers are stated to be instrumental in cardiac damage diagnosis.…”
Section: Cytokine Stormmentioning
confidence: 99%